Positron Impact Excitation Cross Section of Helium - and S. Saxena, K. Kumar, (Recent Research in Science and Technology, 2010)
We have computed excitation cross section (ECS) of Helium (21S - 21P and 23S - 23P) by positron impact using coupled channel optical (CCO) method. Here we have compared the calculated ECS results for singlet-singlet excitation with other available theoretical data. The results are found in excellent agreement with convergent close coupling (CCC) and distorted wave approximation (DWA) calculations. For triplet-triplet transition, we have compared our results with available experimental results also. However some discrepancies suggested that more theoretical work is required in future.